Effect of fiber alignment in gelled electrospun membranes based on poly(vinylidene fluoride) for battery applications - Costa, Carlos M. (2013)
Battery separators based on electrospun membranes of poly(vinylidene ﬂuoride) (PVDF) have been prepared in order to study the effect of ﬁber alignment on the performance and characteristics of the membrane. The prepared membranes show an average ﬁber diameter of 272 nm and a degree of porosity of 87 %. The gel polymer electrolytes are prepared by soaking the membranes in the electrolyte solution. The alignment of the ﬁbers improves the mechanical properties for the electrospun membranes. Further, the microstructure of the membrane also plays an important role in the ionic conductivity, being higher for the random electrospun membrane due to the lower tortuosity value. Independently of the microstructure, both membranes show good electrochemical stability up to 5.0 V versus Li/Li+. These results show that electrospun membranes based on PVDF are appropriate for battery separators in lithium-ion battery applications, the random membranes showing a better overall performance.